2015
DOI: 10.1088/0957-4484/26/43/434002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ALD-grown Al2O3on the refractive index sensitivity of CVD gold-coated optical fiber sensors

Abstract: The combined effect of nanoscale dielectric and metallic layers prepared by atomic layer deposition (ALD) and chemical vapor deposition (CVD) on the refractometric properties of tilted optical fiber Bragg gratings (TFBG) is studied. A high index intermediate layer made up of either 50 nm or 100 nm layers of Al2O3 (refractive index near 1.62) was deposited by ALD and followed by thin gold layers (30-65 nm) deposited from a known single-source gold (I) iminopyrrolidinate CVD precursor. The fabricated devices wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Continuous hot‐wire chemical vapor deposition (CVD) is a versatile method for deposition protective coatings (eg, Al 2 O 3 , BN, TiC) and functional films (eg, Au, In 2 O 3 ) onto structural and optical fibers, and widely adopted to fabricate boron, diamond, and SiC monofilaments . Different to the static metallic wires used in commercialized catalytic CVD method, which are mainly used to activate the ambient gas phase, the moving wire acts as both an energy source and the substrate for the growth of deposit during the process of coating and monofilament fabrications.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous hot‐wire chemical vapor deposition (CVD) is a versatile method for deposition protective coatings (eg, Al 2 O 3 , BN, TiC) and functional films (eg, Au, In 2 O 3 ) onto structural and optical fibers, and widely adopted to fabricate boron, diamond, and SiC monofilaments . Different to the static metallic wires used in commercialized catalytic CVD method, which are mainly used to activate the ambient gas phase, the moving wire acts as both an energy source and the substrate for the growth of deposit during the process of coating and monofilament fabrications.…”
Section: Introductionmentioning
confidence: 99%
“…Gold metal is a highly effective corrosion-resistive material due to its high electrical and thermal conductivity. Thin films and nanomaterials of gold have found some wide range applications such as in optical devices [4,6,8], power sources [151], microelectronic devices [2][3][4][5][6][7][8][9][10] and so on. In the end of last century, Haruta et al [152][153][154] have revealed that gold nanoparticles with diameters less than 10 nm, uniformly dispersed in metal oxides exhibit high catalytic activity in the reaction of CO oxidation at low temperature.…”
Section: Applications Of Volatile Compound Of Gold In Cvd/ald Processesmentioning
confidence: 99%
“…Thin films deposited onto substrates held at 350°C were confirmed by P-XRD and XPS to be pure gold metal films consisted of densely packed particles less than 50 nm in diameter. Mandia et al [10] have also used the same precursor for the deposition of thin gold films due to its advantages, which include thermal on HSAS was only about 10% at 100 o C. Those processes have influenced the growth rate and purity of metal films prepared from that type of precursors. Compound AuMe 3 PMe 3 was also used in CVD to produce gold nanoparticles with plasmonic properties on amine-terminated surfaces for biosensing applications [38].…”
Section: Fig 36mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some semiconductor oxide based thin films have been applied intensively to fabricate optical fiber based sensors, for example ZnO [11], In2O3, WO3 [12], Al2O3 [13]. SnO2 coated single mode optical fiber also has also been used to study the LMR effect to measure the relative humidity within near Infra-red region approximately (in the range of 1400-1600), observing the first LMR in 1550 nm and sensitivity of 1.9 nm/%RH [14,15].…”
Section: Introductionmentioning
confidence: 99%